2020
DOI: 10.1101/2020.03.21.001123
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potentiating the anti-tumor response of tumor infiltrated T cells by NAD+supplementation

Abstract: Tumor immunotherapies have provided clinical benefits, yet great potential remains for optimizing therapeutic effects. Here, we show that low NAD + levels restrict the function of 20 tumor infiltrating T lymphocytes (TILs). TILs harvested from human ovarian tumor tissues showed decreased NAD + levels compared with T cells from paired peripheral blood samples.The combination of whole-genome CRISPR and large-scale metabolic inhibitor screens implicated the NAD + biosynthesis enzyme nicotinamide phosphoribosyltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…Interestingly, NAD + intracellular levels were restored by adding NAD + to the culture medium, thus suggesting that T cells are able to uptake NAD + from the environment. This was able to restore T cell activation, confirming that high NAD + levels are essential for T cell activation (31). Appealing results were obtained by comparing the NAD + levels of tumor infiltrating lymphocytes (TIL) and peripheral blood lymphocytes (PBL), in samples from ovarian cancer patients and from melanoma preclinical models.…”
Section: The Direct Role Of Nad +mentioning
confidence: 73%
See 2 more Smart Citations
“…Interestingly, NAD + intracellular levels were restored by adding NAD + to the culture medium, thus suggesting that T cells are able to uptake NAD + from the environment. This was able to restore T cell activation, confirming that high NAD + levels are essential for T cell activation (31). Appealing results were obtained by comparing the NAD + levels of tumor infiltrating lymphocytes (TIL) and peripheral blood lymphocytes (PBL), in samples from ovarian cancer patients and from melanoma preclinical models.…”
Section: The Direct Role Of Nad +mentioning
confidence: 73%
“…A novel study analyzed the role of NAD + in the activation of the anti-tumor T cell response (31). Genetic and metabolic analysis of the Jurkat T-ALL cell line allowed the genes involved in T cell activation to be identified.…”
Section: The Direct Role Of Nad +mentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, a G0S9 product was identified as NAMPT, an enzyme mediating salvage synthesis of NAD + . 29,30 This indicated an early need for NAD + , a conclusion recently confirmed by Yuetong Wang et al 31 Unaware of our G0S9 work, from their search 'to identify genes involved in the regulation of T cell activation', Wang et al 31 concluded that 'the NAD + biosynthesis enzyme nicotinamide phosphoribosyltransferase (NAMPT) is required for T cell activation'. Indeed, specific inhibitors of NAMPT (eg FK866) were 'ranked among the most disruptive compounds to T cell activation', with CD8 T cells being more sensitive than CD4 T cells.…”
Section: Reprogramming Involves Activation Genesmentioning
confidence: 75%
“…Wang et al 31 went further. Rather than lectin, they employed anti-CD3 and anti-CD28 antibodies to polyclonally activate human T cells in vitro.…”
Section: Reprogramming Involves Activation Genesmentioning
confidence: 99%